REPORT ON THE MAP OF WEST ONGUL ISLAND - Arao YOSHIDA; Yoshio SAITO (National Institute of Polar Research, 1965)
0ne sheet map of West Ongul Island, separated by a narrow strait from East Ongul Island in which Syowa Station is situated, was compiled with 1 : 5,000 scale. The plotting, based on 4 ground control points and 2 models of vertical air photographs taken by the 6 th Japanese Antarctic Research Expedition, was carried out by using a Wild Stereo Plotter.